Degradation of sulfolane in aqueous media by integrating activated sludge and advanced oxidation process. (May 2019) - Khan, Muhammad Faizan; Yu, Linlong; Achari, Gopal; Tay, Joo Hwa
Abstract: In this study, the performance of an integrated technology, combining biological treatment with advanced oxidation process in sequence, was evaluated for the degradation of sulfolane in aqueous media. In addition, the impact of biological process on AOP was also studied by assessing residual sulfolane, nutrient and total suspended solids (TSS) concentrations. The integration of activated sludge process with UVC/H2 O2 resulted in more than 81% of sulfolane degradation in less than 24 h. It was observed that mineralization was much faster in biological system compared to AOP. Mechanistically, the process of degradation is different in the two processes as various by-products were identified during UVC/H2 O2 but not during the biological process. The impact of residual sulfolane concentration on UVC/H2 O2 was significant beyond a concentration of 30 mg L −1, while below 30 mg L −1 the rate of degradation was independent of sulfolane concentration. Residual nutrients from biological systems did not impact AOP performance. Nevertheless, presence of TSS >44 mg L −1 had a negative impact on the performance of UVC/H2 O2 by reducing UV transmittance which led to retardation of sulfolane degradation. The application of UVC/H2 O2 after biological treatment was an advantage as UVC/H2 O2 could perform dual roles of oxidant and disinfectant. Graphical abstract: Image 1 Highlights: Integrated activated sludge - UV/H2 O2 treatment can effectively degrade sulfolane. Residual nutrients do not affect UV/H2 O2 performance. High initial sulfolane and biomass concentration can impact UV/H2 O2 performance. Sulfolane is absorbed by microbes prior to being metabolized. UV/H2 O2 can degrade sulfolane and disinfect post biotreated water simultaneously.